ANALISIS POTENSI REGENERASI POHON DI HUTAN KOTA UNIVERSITAS INDONESIA - Tirta Suganda (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2016)
A study of tree regeneration potential in urban forest of Universitas Indonesia was conducted in Februari—April 2014. Location was established was divided into 42 quadrats 20x20 m each which used to obtain trees data, plots of 10x10 m each which used to obtain pole data, plots of 5x5 m each which used to obtain sapling data, and plots of 2x2 m each which used to obtain seedlings data. The secondary data was processed to obtain vegetation data, and tree regeneration analysis then conducted. We recorded 417 individuals of trees seedling, representing 36 species and 17 family. Three species which had highest density of seedlings were Intsia bijuga Kuntze. (80), Hevea brasiliensis Muell. Arg. (56), and Ficus hirta Vahl (46). At the sapling stage, 387 individuals were recorded representing 43 species and 22 family. Three species which had highest density of saplings were Ficus hirta (55), Psychotria viridiflora Reinw. Ex Bl. (41), and Grewia tomentosa Juss. (41). At the pole stage, 76 individuals were recorded representing 29 species and 15 family. Three species which had highest density of poles were Swietenia mahagoni (L.) Jacq. (12), Grewia tomentosa (10), and Macaranga tanarius (L.) Mull. Arg. (7). Forest tree regeneration ability in urban forest of Universitas Indonesia was counted into a good category. A total of 23 species (69,7%) of 33 tree species were regenerating in plot and 9 species (27,27%) have a complete regeneration phase. Fabaceae , Euphorbiaceae, Tiliaceae, dan Moraceae were a family that has a good potential for regeneration and will filling the forest in the future.Keywords : vegetation analysis, urban forest, tree regeneration